Nasarawa Audience Perception of Citizen Journalists’ Reportage of Climate Change on Select Social Media Platforms in Nigeria - Joy, Iduh Ene; Ogande, Anthony; Akpede, K. S. (ALSYSTECH Journal of Education Technology, 2025)
This study investigates audience perceptions of citizen journalists’ reportage of climate change on select social media platforms in Nasarawa State, Nigeria. The research aims to assess how citizen journalism shapes public understanding of climate change through digital channels. Employing a survey design with questionnaires as the primary instrument, the study reveals that audiences in Nasarawa State perceive climate change reportage on YouTube, X (formerly Twitter), and Facebook as both effective and satisfactory. However, the findings also indicate that not all climate change information disseminated through these platforms is accurate. The study concludes that social media serve as a double-edged tool in climate change communication, offering both credible insights and the risk of misinformation. Nevertheless, these limitations do not diminish the overall credibility of the reported findings. The study contributes to scholarship on media and environmental communication by highlighting the role of citizen journalism in climate change awareness, while underscoring the need for third-party regulation to mitigate misinformation and enhance the reliability of online climate discourse.